2004
DOI: 10.1001/archpedi.158.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Tobacco Use in a Cohort Study of US Adolescent Girls and Boys

Abstract: Our findings indicate that mostly heterosexual adolescents of both sexes and lesbian/bisexual girls are at heightened risk for tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
114
7
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 43 publications
10
114
7
1
Order By: Relevance
“…These results are consistent with observations by Tang et al 4 and remarkably similar to those reported by McKirnan et al 13 but they stand in contrast to those from a school-based survey that found no difference in smoking at least weekly among adolescent boys who self-identify as heterosexual versus gay or bisexual. 9 The reasons underlying this inconsistency are unclear but may reflect differences among studies in the definition and selfidentification of sexual minority status, or in the distribution of participants_ age, race-ethnicity, or indicators of socio-economic status. One report suggests that differences in smoking between adult MSM and male heterosexuals are due in part to access to health care insurance and utilisation, depressive symptoms and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with observations by Tang et al 4 and remarkably similar to those reported by McKirnan et al 13 but they stand in contrast to those from a school-based survey that found no difference in smoking at least weekly among adolescent boys who self-identify as heterosexual versus gay or bisexual. 9 The reasons underlying this inconsistency are unclear but may reflect differences among studies in the definition and selfidentification of sexual minority status, or in the distribution of participants_ age, race-ethnicity, or indicators of socio-economic status. One report suggests that differences in smoking between adult MSM and male heterosexuals are due in part to access to health care insurance and utilisation, depressive symptoms and alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Higher rates of smoking among urban-dwelling lesbians and men who have sex with men (MSM) are suggested by a small number of studies, all from the United States. [3][4][5][6][7][8][9][10][11][12][13] A recent review article identified only three reports pertaining to smoking among MSM. 7 Including reports published subsequently, 4,8,9,[11][12][13] only two employed probability sampling to generate representative samples of MSM.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study we conducted found that mostly heterosexual young women participating in an urban, multiethnic cohort study reported a younger age at first sexual intercourse and first pregnancy, a greater number of lifetime sexual partners, and higher lifetime occurrence of a sexually transmitted disease (STD) than exclusively heterosexual young women. 4 This same study also found that greater risk of childhood sexual abuse reported by the mostly heterosexual female participants did not explain their higher sexual risk compared with the exclusively 1 heterosexual females. These findings led us to undertake the current study using the same analytic sample derived from the Project on Human Development in Chicago Neighborhoods (PHDCN).…”
mentioning
confidence: 83%
“…Literature also clearly documents disparities in smoking among lesbian, gay, and bisexual populations (i.e., sexual minorities) in the United States, suggesting 50%-70% higher prevalence than the general population (Austin et al, 2004;Garofalo, Wolf, Kessel, Palfrey, & DuRant, 1998;Gruskin, Greenwood, Matevia, Pollack, & Bye, 2007;Lee, Griffin, & Melvin, 2009;McCabe, Boyd, Hughes, & d'Arcy, 2003;Skinner, 1994;Stall, Greenwood, Acree, Paul, & Coates, 1999;Tang et al, 2004). Moreover, the American Lung Association (2010) published a special report of tobacco disparities among sexual minorities, harkening a call for more research.…”
Section: Introductionmentioning
confidence: 99%